Genome of Helicobacter pylori and Serotype of HPV Detected in Oropharyngeal and Laryngeal Cancer and Chronic Inflammation Patients - Astl, Jaromír; Holy, Richard; Maute, Eva; Rotnágl, Jan; Kalfeřt, David; Drnková, Barbora; Younus, Temoore; Pavlík, Emil (International journal of environmental research and public health, 2021)
OBJECTIVE: Oropharyngeal/laryngeal carcinoma are common cancers of the upper aerodigestive system. Human papillomavirus (HPV) is described as the most frequent in the cancer of unknown primary. The presence of Helicobacter pylori (HP) in the oral cavity is discussed in some papers. THE AIM OF STUDY: To analyze the incidence of HPV and HP in oropharyngeal/laryngeal cancer persons versus persons with chronic tonsillar inflammation and healthy persons. METHODS: The samples were taken in three groups: (1) tissue of oropharynx/larynx cancer (103 specimens); (2) tissue of palatine tonsils (85 specimens); and (3) healthy control group (50 specimens). We analyzed the presence of HP (PCR) and HPV genomic DNA (Sacace HPV High-Risk Screen Real-TM Quant) in the samples. RESULTS: HP was detected in 86 samples (83.5%) and high-risk HPV in 62 samples (60.2%). We found a very high incidence of HP. In the cancer group, HP was detected in 82.5% cases and HPV positivity in 57.8%. In total, 7.2% of the cancer patients were negative for HP and HPV together. In turn, 53.6% of the cancer patients were positive for HP and HPV together. Four cases (4.2%) were positive for HPV only. VacA positivity was detected in 82 (79.6%) of the cancer cases and VacA negativity in 21 (20.4%) if the cancer cases. The incidence of HP in chronic inflammation (n = 85) was 65 cases (76.5%) and the incidence of HPV was 38 cases (44.7%). VacA positivity was detected in 59 (69.4%) of the chronic inflammation cases and VacA negativity was found in 26 (30.6%) of the chronic inflammation cases. Regarding the control group, we found HP positivity in 5 cases (11.1%) and HPV positivity in 19 cases (42.2%). There was VacA positivity in 6 cases (50.0%) of the control group. Statistically significantly lower prevalence of HP (p < 0.001) and HPV (p = 0.006) was found in the control group. CONCLUSIONS: We suggest that the palatine tonsils are colonized by HP. In our study, HP was present in oropharyngeal cancer in more cases in comparison with HPV infection. The presence of VacA from HP can have an influence on the human epithelial and immune cells' regulation ways. Our results do not support idea that the CagA-positive HP is a primary carcinogen in oropharyngeal area.
Keywords: Inflammation; Papillomaviridae; Oropharynx; human papilloma virus; Helicobacter Infections; zánět; chronic inflammation; Alphapapillomavirus; Papillomavirus Infections; incidence; Serogroup; orofarynx; infekce vyvolané Helicobacter pylori; infekce papilomavirem; Humans; oropharynx; squamous cell carcinoma; Laryngeal Neoplasms; Helicobacter pylori; nádory hrtanu; séroskupina; lidé